2021
DOI: 10.1002/jee.20421
|View full text |Cite
|
Sign up to set email alerts
|

Engineering play with blocks as an informal learning context for executive function and planning

Abstract: Background: Engineering play is an emerging framework for understanding young children's constructive block play as an engineering design process. Few studies have evaluated engineering thinking, language, or behavior in preschool-age children, especially quantitative evaluations that systematically document specific early engineering behavior. More research is needed to support diverse children's engineering education in ecologically valid classroom contexts and understand relations with the key cognitive dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Of the studies that reported on racial demographics, the participants were diverse and typically numbered in the highest percentage of the students being White, then Black, then Latinx, then other. Nine of the studies reported on the socio-economic status of the participants [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies that reported on racial demographics, the participants were diverse and typically numbered in the highest percentage of the students being White, then Black, then Latinx, then other. Nine of the studies reported on the socio-economic status of the participants [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies used another common unit of analysis, caregiver and child. Four of the studies [ 1 , 39 , 41 , 46 ] used educator and child as the units of analysis, and two studies [ 44 , 45 ] used only the caregiver as the unit of analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increasing emphasis on exploring engineering with early childhood learners [1], [2]. The majority of these studies have focused on observing young children playing with building materials [3], [4] or examining engineering in the preschool classroom [5]- [7]. However, few studies [8]- [10] have focused on exploring engineering in the home setting, which is a powerful yet often overlooked learning environment for early STEM learners.…”
Section: Introductionmentioning
confidence: 99%